2020
DOI: 10.1002/stc.2518
|View full text |Cite
|
Sign up to set email alerts
|

An innovative adaptive tuned vibration absorber with variable mass moment of inertia for mitigation of transient response of systems

Abstract: Summary An innovative semiactive device, named the spindle adaptive tuned vibration absorber (SATVA), is proposed herein, having the potential of attenuating unfavorable vibrations of the host systems. The proposed device includes a preferably spindle‐shaped body of mass, whose mass moment of inertia can be altered simply by moving a pair of rotating supports. Therefore, the natural frequency of the device can be altered with a fairly low power consumption. A comprehensive analytical approach is employed in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Research on self-tuning or self-adaptive vibration neutralisers and absorbers can be found in literature, for example [1,2], and this can be achieved in several ways, for example with magnetorheological elastomer (MRE) [3][4][5][6][7][8], with smart materials using shape memory alloy (SMA) [9][10][11][12][13][14][15]. Other ways of doing this involve varying the mass moment of inertia [16], and changing the stiffness element geometry [17][18][19], with rotating spring elements, for example [20][21][22]. Rasooli et al [4] presented a semi-active adaptive tuned vibration absorber consisting of a multilayer sandwich beam with MRE layers and electromagnets attached at the top and bottom layers.…”
Section: Introductionmentioning
confidence: 99%
“…Research on self-tuning or self-adaptive vibration neutralisers and absorbers can be found in literature, for example [1,2], and this can be achieved in several ways, for example with magnetorheological elastomer (MRE) [3][4][5][6][7][8], with smart materials using shape memory alloy (SMA) [9][10][11][12][13][14][15]. Other ways of doing this involve varying the mass moment of inertia [16], and changing the stiffness element geometry [17][18][19], with rotating spring elements, for example [20][21][22]. Rasooli et al [4] presented a semi-active adaptive tuned vibration absorber consisting of a multilayer sandwich beam with MRE layers and electromagnets attached at the top and bottom layers.…”
Section: Introductionmentioning
confidence: 99%
“…A large-span floor structure is proposed as a case study. In [14], it is shown that the innovative adaptive tuned vibration absorber with a variable mass moment of inertia is suitable for the mitigation of the transient response of systems. The adaptive passive variable mass tuned mass damper can control human-induced vertical vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of using a SATMD is to change its properties in order to alter and tune its frequency. This can be done by changing its damping (Hrovat et al, 1983; Abé, 1996; Pinkaew and Fujino, 2001; Setareh, 2002), mass and mass moment of inertia (Ivers et al, 2008; Mohammadi-Ghazi et al, 2012; Shi et al, 2018; Shakib and Ghorbani-Tanha, 2020), and stiffness (Ghorbani-Tanha et al, 2011; Nagarajaiah, 2000; Rafiepour et al, 2014; Walsh and Lamancusa, 1992).…”
Section: Introductionmentioning
confidence: 99%